Analisis Gap Evaluasi Kualitas Sistem E-Learning di Universitas Ibn Khaldun Bogor - Ritzkal Ritzkal; R. Fitria Rachmawati (IndoCEISS in colaboration with Universitas Gadjah Mada, Indonesia., 2022)
A GAP analysis has been conducted on the evaluation of E-Learning systems of LMS UIKA Bogor. Five (5) subjects of discussion in this study, namely include Structured Learning Methods, Unstructured Learning Methods, Population and Samples, E-learning User Activity Record, Evaluation of Results. Process of evaluating the results of a calculation of the System Usability Scale (SUS). Judging from usability or usefulness the e-learning system is feasible. With the following details: a. Based on acceptability ranges, the e-learning falls into the accepted category, b. Based on the grade scale, included in grade C where the SUS score produced is 79, c. Based on adjective ratings, the value is between a score of 70-80 which means it falls into the range of good categories. The results of the usability evaluation of LMS UIKA Bogor products stated that overall, were acceptable or feasible.